2017
DOI: 10.1017/jfm.2017.386
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-induced vibrations of a cylinder in planar shear flow

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 18137 The system composed of a circular cylinder, either fixed or elastically mounted, and immersed in a current linearly sheared in the cross-flow direction, is investigated via numerical simulations. The impact of the shear and associated symmetry breaking are explored over wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Upstream shear has been shown in experiments to delay the onset of periodic vortex shedding, the Reynolds number at which the Hopf bifurcation occurs Re H increasing with K to the point that shedding can be completely suppressed all the way up to Re < 220 1 . This effect has also been observed in numerical simulation 2,50 . Other computational studies, however, did not detect the phenomenon despite exploring similar values of the parameters 36,40 .…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Upstream shear has been shown in experiments to delay the onset of periodic vortex shedding, the Reynolds number at which the Hopf bifurcation occurs Re H increasing with K to the point that shedding can be completely suppressed all the way up to Re < 220 1 . This effect has also been observed in numerical simulation 2,50 . Other computational studies, however, did not detect the phenomenon despite exploring similar values of the parameters 36,40 .…”
Section: Introductionsupporting
confidence: 77%
“…There is some controversy as to the dependence of C d of the circular cylinder on the shear parameter. Several experimental 3,37,39,47 and numerical 36,38,[48][49][50] studies have shown a decreasing trend, in some cases marginal, with K. Others 2,43,45 show the exact reverse trend. Free-stream turbulence levels, which are often dependent on the prescribed shear parameter, might be playing an important role in experimental results 39,43 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…2014; Zhang et al. 2014; Gsell, Bourguet & Braza 2017). These studies have revealed significant effects on the dynamic behaviour and the resultant fluid and structural forces in the presence of shear flow.…”
Section: Introductionmentioning
confidence: 99%